Pengaruh Store Atmosphere dan Store Image terhadap Keputusan Pembelian Konsumen pada Toko Buku Gramedia Pondok Indah - Maretha, Vitta; Kuncoro, Engkos Achmad (Bina Nusantara University, 2011)
This research is to identify the influence of store atmosphere (X1) and store image (X2) towards consumers purchase decision (Y) in Gramedia bookstore Pondok Indah. The method used in this research is descriptive method, with multiple regression analysis technique, through using data gathered from distribution questionnaire to 100 samples of consumers in Gramedia bookstore Pondok Indah. The analysis result showed that store atmosphere and store image have significant influent towards consumers purchase decision in Gramedia bookstore Pondok Indah. In other words, the purchase decision of consumers in Gramedia bookstore Pondok Indah is influenced significantly by store atmosphere and store image in the mind of the consumers.Â